Representaton of Family Values in Polish Paremiological Units with Semantically Opposite Components - Moroz, Tetiana (Poznańskie Studia Slawistyczne, 2021)
This paper presents the results of the research of the concept of family and basic family values in Polish paremiological proverbs with semantically opposite components. More than 60 paremiological units with semantically opposite components were analysed. Considering the semantics of paremias, there are groups that represent the image of the Polish family, i.e. “Husband and wife (the relationship between them)”, „Parents and children (the importance of parents for children)”, „Parents and children (the importance of children for parents)”, „Relationships between other relatives”. The analysis of these groups has showed the breadth of the semantic structure of paremias with antonymous components, which reflect the relationship between husband and wife, the peculiarities of the family hierarchy; a significant difference between the importance of father and mother for a child, in particular the status and functions of father and mother; the importance of children in parents’ lives; relationship between brother and sister and between two brothers as well, and the images of blood relatives and relatives by marriage.